The Appositional Articular Morphology of the Talo‐crural Joint: The Influence of Substrate Use on Joint Shape. Issue 4 (30th January 2014) - Turley, Kevin; Frost, Stephen R.
ABSTRACT The appositional articular morphology of the talo‐crural joint is the third component of the joint complex. It is a site of internal integration of this highly stable functional evolutionary unit. Prior studies of the other two components, tibia and talus, demonstrated that substrate preference influenced their articular shape. This effect was unrelated to physical attributes (size and mass) and phylogeny (superfamily). The effect of this behavioral factor, substrate preference, on shape and integration of the appositional articular morphology was investigated. Two hundred forty‐five matched distal tibial and proximal talar landmarked surfaces from 12 diverse Catarrhine taxa were studied. Shape effects due to the same factors previously studied were examined in the tibial and talar subsets and were highly significant (P < 0.0001). These were assessed using Multivariate Regression and Relative Warps analysis, and Permutation tests, with results consistent with prior unmatched cohorts. Substrate preference influenced shape and was unrelated to the other factors across taxa. Singular Warp analysis of the cross‐covariance matrix revealed sorting of taxa by substrate use, unrelated to physical attributes and phylogeny. Finally, the sorting demonstrated a signal of convergent evolution among distantly related taxa and divergent evolution among closely related taxa reflecting substrate use. Results were consistent with a behavioral influence, substrate use, affecting articular shape and integration in this highly stable functional evolutionary unit, and signals with evolutionary implications. Anat Rec, 297:618–629, 2014. © 2014 Wiley Periodicals, Inc.